Children with Disabilities in Digital Era: A Perspective for Physical Education - Acharya, Yadav (Tribhuvan University Journal, 2022)
This study critically analyzes the prospect of physical education for children with disabilities in a digital era. A qualitative design was used to explore the in-depth information. Both primary and secondary data were applied. This study covers blind, deaf and physically disabled students. Altogether 22 key informants and participants were selected for the first-hand information. The data are analyzed and interpreted based on themes by using critical discourse analysis and narrative techniques. The study found that digital technology as the main cause of physical inactivity. Physical activities are essentially needed for children with disabilities especially those who tend to be less physically active and are at higher risk of inactivity complications for coping with the challenges posed by the technology. The study further recommended teachers and parents of children with disabilities to increase outdoor activities so that they can be physically active.